Medieval Trade in the Eastern Mediterranean and Beyond - Jacoby, David, author.
1 online resource (xvi, 362 pages)
Keywords: "The articles in this collection cover the region extending from Italy to the Black Sea and to Egypt, over a period of seven centuries, with an emphasis on the considerable economic and social interaction between the West and the regions of the Eastern Mediterranean. They represent key works in the oeuvre of David Jacoby, the doyen of scholars in the field over many decades."--Provided by publisher.